Factibilidad técnica de implementación de smart metering en el área urbana residencial con tecnologías de comunicación inalámbrica 4G - Pérez Cáseres, Gonzalo Vicente (2015)
The Implementation of Smart Metering is a more accurate, efficient and obtain power consumption information important in advanced metering infrastructure that incorporates the Smart Grid technological advance electronic meters are able to obtain measurements of energy from one form electrical real-time implementation of 4G technology and communication transmitted through communication protocols into the system data management at the same time, provide data distribution companies to control the ability to detect problems in their systems and manage demand end to operate efficiently.